2007
DOI: 10.1614/wt-06-074.1
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Early Season Multispectral Images for Weed Detection in Corn

Abstract: The objective of this research was to determine the potential use of commercially available multispectral images to detect weeds at low densities during the critical period of weed control. Common lambsquarters seedlings were transplanted into plots of glyphosate-resistant corn at 0, 1, 2, and 4 plants/m2at two sites, Agronomy Center for Research and Extension (ACRE) and Meig's Horticultural Research Farm at the Throckmorton–Purdue Agricultural Center (TPAC), in Indiana. Aerial multispectral images (12 to 16 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…1.14 cm by 1.14 cm) and 2.62 cm 2 , and 14.44 and 30.3 cm 2 of actual ground area, respectively in the corresponding images. Considering that the smaller GSD had the higher spatial resolutions, any of these spatial resolutions were noticeably higher than those obtained by Armstrong et al (2007), who used multispectral images from a piloted aircraft flying at a 300 m altitude in maize fields for weed detection in the early season.…”
Section: Johnsongrass Detection and Mapping As Affected By Spatial Anmentioning
confidence: 71%
See 1 more Smart Citation
“…1.14 cm by 1.14 cm) and 2.62 cm 2 , and 14.44 and 30.3 cm 2 of actual ground area, respectively in the corresponding images. Considering that the smaller GSD had the higher spatial resolutions, any of these spatial resolutions were noticeably higher than those obtained by Armstrong et al (2007), who used multispectral images from a piloted aircraft flying at a 300 m altitude in maize fields for weed detection in the early season.…”
Section: Johnsongrass Detection and Mapping As Affected By Spatial Anmentioning
confidence: 71%
“…The images captured by Armstrong et al (2007) from that altitude resulted in pixel resolutions that ranged from 12.1 (146.41 cm 2 of ground area) to 16.7 cm (278.9 cm 2 of ground area), depending on slight variances in the altitude of the aircraft. With those GSD, the reliable early weed patch detection was not achieved, and they concluded that refinements in the sensor spatial and spectral resolutions were necessary to increase the ability to successfully detect early season weed infestations; a specific suggestion was that enhancement could be provided with ground-based systems.…”
Section: Johnsongrass Detection and Mapping As Affected By Spatial Anmentioning
confidence: 99%
“…Agricultural weeds are often patchily distributed within a field (Cousens and Mortimer, 1995) and local dispersal around the parent results in patches that persist over many years (Wilson and Brain, 1991). With increasing interest in ecological weed management and site-specific management, research is currently developing tactics and technologies to spray only dense patches of weeds ("patch spraying") and to leave other areas unsprayed (Andújar et al, 2011;Armstrong et al, 2007;Brown and Noble, 2005). The ability to predict the distribution of weeds could aid decisions on the spraying of weed patches, particularly where pre-emergence herbicides are to be used (Oriade et al, 1996;Paice et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As scouting for, and counting, weeds is time consuming (Timmermann et al, 2003;Wyse-Pester et al, 2002) some form of machine-based weed detection is necessary (Gerhards and Oebel, 2006). Weed detection can be performed using remote (Armstrong et al, 2007), optoelectronic (Blackshaw et al, 1998), UV-induced fluorescence (Longchamps et al, 2010) or digital imaging sensors (BurgosArtizzu et al, 2009;Panneton and Brouillard, 2009;Schuster et al, 2007). All of these techniques require weed/crop discrimination.…”
Section: Introductionmentioning
confidence: 99%